A Certificate-Based Provable Data Possession Scheme in the Standard Model. (2nd September 2021) - Zhou, Caixue
Abstract : Certificate-based cryptosystem can not only resolve the private key escrow problem inherent in the identity-based cryptosystem but also reduce the cost of public key certificate management in the public key infrastructure-(PKI-) based cryptosystem. Provable data possession (PDP) can ensure the integrity of users' data stored in the cloud at a very high probability. By combining these two concepts, we propose a certificate-based PDP scheme. We prove that our scheme is secure in the standard model assuming that the Squ-CDH problem is hard. Based on the index logic table, our scheme can be extended to support dynamic operations easily. Efficiency analysis shows that our scheme has high efficiency.